2021
DOI: 10.3389/fbioe.2021.800265
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Cellulase From Bacillus subtilis Strain and its Effect on Digestibility and Structural Modifications of Lignocellulose Rich Biomass

Abstract: Microbial cellulases have become the mainstream biocatalysts due to their complex nature and widespread industrial applications. The present study reports the partial purification and characterization of cellulase from Bacillus subtilis CD001 and its application in biomass saccharification. Out of four different substrates, carboxymethyl cellulose, when amended as fermentation substrate, induced the highest cellulase production from B. subtilis CD001. The optimum activity of CMCase, FPase, and amylase was 2.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 67 publications
5
25
0
Order By: Relevance
“…Increased peak intensities in the amorphous and crystalline regions of 4-Cl-OPD modified HSA demonstrated the formation of complex structures formation compared to native HSA. As a result, XRD findings confirmed significant structural changes in HSA after 4-Cl-OPD modification ( Gong et al, 2011 ; Malik and Javed, 2021 ).…”
Section: Discussionmentioning
confidence: 54%
“…Increased peak intensities in the amorphous and crystalline regions of 4-Cl-OPD modified HSA demonstrated the formation of complex structures formation compared to native HSA. As a result, XRD findings confirmed significant structural changes in HSA after 4-Cl-OPD modification ( Gong et al, 2011 ; Malik and Javed, 2021 ).…”
Section: Discussionmentioning
confidence: 54%
“…That's why the addition of EDTA inhibit the activity of enzymes and it suggested that cellulase enzyme activity is metal cofactor dependent (Elbanna et al 2015). The inhibitory impact of ionic surfactant SDS is attributed to the distortion in the protein active site by nonspecific interactions, causing conformational changes which result in protein unfolding and instability, the same finding was documented by (Malik and Javed 2021).…”
Section: Discussionmentioning
confidence: 77%
“…The cellulase produced by NBCB1 remained active in a wide range of pH (3.5-9.5) and temperature (4-80 o C), which is a desirable characteristic for industrial applications [45]. The enzyme had pH and temperature optima of 5.…”
Section: Discussionmentioning
confidence: 99%